Reading Sophie Robinson Through Frank O'Hara's 'Ploop!'. Issue 10 (2nd October 2020) - Kane, Daniel
ABSTRACT: Frank O'Hara's 1959 'POEM (Wouldn't it be funny)', is, at first glance, adamantly minor and wilfully juvenile. And yet, as I argue in the first section of this essay, O'Hara's 'POEM' and related works have much to say about abjection and silliness as a form of politics. O'Hara's texts also serve to repudiate the romantic equation of poet as prophet that through the 1950s and 1960s defined writers as various as Ezra Pound, Allen Ginsberg and Dylan Thomas. O'Hara upends poets' efforts both to represent a falsely universalised human condition and, correspondingly, to frame poetry as hierarchically superior to other artistic genres. The second section of the essay notes O'Hara's prominence in the United Kingdom and moves on to consider specifically how O'Hara's poetry has influenced the work of Sophie Robinson, a significant figure in British innovative poetry networks. Robinson, this essay concludes, positively applies and adapts O'Hara's invocation of the abject to her own project, in part by advancing a progressive politics that appears however complexly and elusively in her verse.